Vegetativnaja reguljacija kardiorespiratornoj sistemy v dinamike godicnogo trenirovocnogo cikla - Romanchuk, A. P. (Teorija i Praktika fiziceskoj Kul'tury, 2005)
In the given work the analysis of the results of the research of the vegetative regulation of cardiorespiration system with the help of spiroarterio- cardiorythmography is carried out in dynamics of a training cycle of a year. According to the change of the parameters of ratio LF/HF of variability of a cardiac rhythm, systolic and diastolic arterial pressure, and also spontaneous respiration, the analysis is carried out for ranking distributions and correlation matrixes which has allowed to determine the features of the regulator influences of the vegetative system on the cardiovascular and respiratory systems in dynamics of a year's training cycle.